Peran strategi pembelajaran terhadap keterampilan pengendalian objek ditinjau dari koordinasi pada anak - Putri, Marisadiana; Bakhtiar, Syahrial; Bafirman, Bafirman; Ihsan, Nurul; Pratama Putri, Lucy (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
The ability to control objects is an ability that children must master. Mastery of object control is obtained from one of them from the learning process obtained at school. This learning process can provide students with learning strategies. The study aimed to determine the effect of learning strategies and coordination skills on the ability to control objects in children in elementary school. This research method is quasi-experimental, involving 60 male and female students in grade 5, and the sampling technique used is total sampling. The instruments used in this study on object skills used the test of gross motor development 2nd edition subtest. Movement coordination data uses instruments consisting of anthropometry, balance beams, moving sideways, jumping sideways, and eye-hand coordination. The data were analyzed using the two-way analysis of variance (ANOVA) technique with the help of SPSS 26. Based on the research findings, the TGfU learning approach group had the best average score of 33.86 among other groups. The conclusions of this study show that the object control ability of students with low coordination is better if given conventional learning strategies than TGfU, as evidenced by a value (p < 0.05). The conclusion that can be drawn from this study is that TGfU learning strategies influence the ability to control objects in children in elementary school, and there is an interaction between coordination and learning strategies.